Characterisation of microsatellite and SNP markers from Miseq and genotyping-by-sequencing data among parapatric Urophora cardui (Tephritidae) populations - Johannesen,Jes; Fabritzek,Armin G.; Ebner,Bettina; Bikar,Sven-Ernö (PeerJ, 2017)
Phylogeographic analyses of the gall fly Urophora cardui have in earlier studies based on allozymes and mtDNA identified small-scale, parapatrically diverged populations within an expanding Western Palearctic population. However, the low polymorphism of these markers prohibited an accurate delimitation of the evolutionary origin of the parapatric divergence. Urophora cardui from the Western Palearctic have been introduced into Canada as biological control agents of the host plant Cirsium arvense. Here, we characterise 12 microsatellite loci with hexa-, penta- and tetra-nucleotide repeat motifs and report a genotyping-by-sequencing SNP protocol. We test the markers for genetic variation among three parapatric U. cardui populations. Microsatellite variability (N = 59 individuals) was high: expected heterozygosity/locus/population (0.60–0.90), allele number/locus/population (5–21). One locus was alternatively sex-linked in males or females. Cross-species amplification in the sister species U. stylata was successful or partially successful for seven loci. For genotyping-by-sequencing (N = 18 individuals), different DNA extraction methods did not affect data quality. Depending on sequence sorting criteria, 1,177–2,347 unlinked SNPs and 1,750–4,469 parsimony informative sites were found in 3,514–5,767 loci recovered after paralog filtering. Both marker systems quantified the same population partitions with high probabilities. Many and highly differentiated loci in both marker systems indicate genome-wide diversification and genetically distinct populations.
Keywords: Parapatry; Genetic cline; EcoR1; Genome-wide differentiation; Urophora cardui; Alternative sex-linked locus; SSR; GBS